Statistics for engineering and the sciences - Mendenhall, William. 4 0 16; Sincich, Terry; 5 (Upper Saddle River, N.J. : Pearson Prentice-Hall, 2007)
This text is designed for a two-semester introductory course in statistics for students majoring in engineering or any of the physical sciences. Inevitably, once these students graduate and are employed, they will be involved in the collection and analysis of data and will be required to think critically about the results. Consequently, they need to acquire knowledge of the basic concepts of data description and statistical inference and familiarity with statistical methods they are required to use on the job.
Includes bibliographical references (p. 1028-1035) and index.
Keywords: 2 -- 0; 6; Statistical methods. -- Mathematical statistics.;Engineering -- 20; 20; 2